Philosophy of the Indic and Sufi Thought in the Islamic World - An Analysis of the Commonalities on the Ground of Spiritual and Religious Thought - Abdelqadir Houti; Issam Okleh (Journal of Islamic Thought and Civilization, 2024)
This research investigates the subject of the dialogue between the Indic and Sufi philosophies in the Muslim world and common theological and metaphysical backgrounds of the two traditions. Both Indic and Sufi traditions are based on the denial of the physical world, the sanctity of an individual and the achievement of the state of unity. The research is focused on the ontological side of the two traditions and their views on spirituality; non-dualism in Vedanta and tawhid in Sufism, their views on self, worship and the way to the divine. The study also captures the historical and cultural interaction that made it possible for the two traditions to touch each other intellectually and spiritually with special focus on the spread of Islam in South Asia. By analyzing these similarities this research conclude that Indic and Sufi philosophies offer two different ways of understanding the divine, human being and salvation. This comparative study helps readers to understand some of the syncretistic traditions that are part of the religious experience of the Islamic world and to better appreciate the complex patterns of religions of the world.